Tax Review Models and Working Papers in the Framework of Preparation for A Tax Audit (Case Study PT BJS) - Wauran, Anita Ludia Vivian; Langi, Treesje Amelia Clara; Wagiu, Decire Dumingkan; Lasut, Jeane Christine; Rengku, Jeffry; Kaligis, Stevie; Toweula, Alpindos (Future Science, 2022)
The existence of an examination letter addressed to the Industry as a taxpayer is a scourge that is very much feared by every taxpayer as a business actor receiving income. The existence of an audit means problems for the Industry as a taxpayer, ignorance of the rules and mistakes that may occur either intentionally or unintentionally in reporting Industrial taxes will eventually become a very feared scourge. The existence of payment of the principal tax that must be paid after the tax audit, as well as very large fines and sanctions due to the reporting errors in a very large amount, has disrupted the cash flow of the industry. So as to minimize errors and confusion in tax reports regarding fiscal financial reports that are reported to the Directorate General of Taxes (DGT) in the form of SPT, then prior to the existence of an audit letter it is better to hold a tax review contained in the working papers, to review or examine what tax obligations are inherent in every transaction that is in the commercial financial reports produced by the Industry, prior to reporting taxes. So that if there is a tax audit by the DGT on income from these business activities, a review or review of the tax payable that may exist in every transaction of the Industry's financial statements has been carried out beforehand, so that fines or sanctions that may arise can be minimized or prevented from the start. Ignorance of the need for a tax review model by the Industry made researchers conduct research on the tax review model and working papers in accordance with applicable tax regulations, in the face of a tax audit for Industry as a taxpayer and IDUKA. This research method uses a qualitative descriptive method, which begins with designing a tax review in working papers for financial reports prepared by the industry as a taxpayer. The results of this study produce a tax review model with audit work papers in preparing tax audits which are expected to assist taxpayers in planning corporate taxes.